American industry : structure, conduct, performance - Caves, Richard E. (Englewood Cliffs, N. J.: Prentice-Hall, 1964)
The book examines the topics for foundation of economics and its analytical core, Price theory and National Income Analysis..
Includes index
Includes bibliographical references
usc 25/01/2019
Loans
Keywords: Industries; Restraint of trade; Industrial concentration; United States